2011
DOI: 10.2967/jnumed.110.081539
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of the Gastrointestinal Absorption of Orally Administered Drugs in Conscious and Anesthetized Rats

Abstract: This study assessed the process of gastrointestinal drug absorption in vivo using PET. Methods: 18 F-FDG was used as a model probe and was orally administered to rats as a solution. PET scans were obtained of the whole body and abdominal region under conscious and anesthetized conditions. Blood samples were routinely taken from the femoral vein during scanning. The rate of gastric emptying and intestinal absorption of 18 F-FDG was estimated from the time profiles of radioactivity in the stomach and small intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
1
38
2
Order By: Relevance
“…In recent years, it was reported that this technique is also useful for the assessment of the oral drug absorption process in vivo. [28][29][30] In the present study, the accumulation of I were not observed at 0-0.5 h, but were observed at 2-3, and 4-5 h after an administration. The ROI analysis shows that at least 11.7% of [Zn(Cq) 2 ] was dissociated in the body at 2-3 h after an administration (Table 2).…”
contrasting
confidence: 61%
“…In recent years, it was reported that this technique is also useful for the assessment of the oral drug absorption process in vivo. [28][29][30] In the present study, the accumulation of I were not observed at 0-0.5 h, but were observed at 2-3, and 4-5 h after an administration. The ROI analysis shows that at least 11.7% of [Zn(Cq) 2 ] was dissociated in the body at 2-3 h after an administration (Table 2).…”
contrasting
confidence: 61%
“…With the development of dedicated small-animal PET scanners, it is possible to perform functional imaging in small animals at high spatial resolutions (26)(27)(28). Using a small-animal PET imaging system, we obtained the first evidence-to our knowledge-that disulfiram pretreatment efficiently corrects inappropriate copper biodistribution in living MD model mice.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the evaluation of absorption, distribution, metabolism, and excretion in the development of pharmaceuticals has involved autoradiography of the whole body and the detection of radioactivity associated with dissected tissues by use of radioactive 125 I-or 111 In-labeled pharmaceuticals (25). However, recently developed molecular imaging technologies allow the visualization and quantitative measurement of biologic processes in living systems (26)(27)(28). Radioisotope-based molecular imaging techniques, such as PET, have been used for the noninvasive detection of pharmacodynamics in the gut and for the determination of functional changes in the nervous system (26,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although minimally-invasive methods can measure GI absorption, such as gamma-scintigraphy (9)(10)(11) and magnetic resonance imaging (12), these methods are insufficiently quantitative and lack of spatial or temporal resolution. We previously showed that the GI transit rate of drugs can be measured directly by that positron emission tomography (PET), a minimally invasive and highly sensitive method with good spatio-temporal resolution (13)(14)(15)(16). For example, 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) PET has been utilized in rats (13) and humans (14); PET with deoxy-[ 18 F]fluoropoly(ethylene glycol)s, having an average mass of 2 kDa, has been used in rats (15); and PET has been used to monitor the hepatic distribution of [ 11 C]telmisartan in rats (16).…”
Section: Introductionmentioning
confidence: 99%